How older adults self-manage distress – does the internet have a role? A qualitative study - Alice Moult; Heather Burroughs; Tom Kingstone; Carolyn A. Chew-Graham (BMC Family Practice, 2018)
Abstract Background Anxiety and depression are common in older adults, but often under-recognised by GPs. Rather than perceiving themselves as suffering from anxiety or depression, older adults are more likely to self-identify as experiencing low mood, stress or distress. Older people may also feel responsible for managing their own mood problems. The Internet has the potential to support the self-management of distress through accessing health information or social support. Methods This study was approved by Keele University’s ethical review panel. Older adults who self-identified as experiencing distress were recruited from community groups in the West Midlands, England. To generate data, ‘think-aloud’ methods (including storyboards and an extract from an online forum) were embedded within semi-structured interviews. Thematic analysis, incorporating constant comparison methods, were used for data analysis. Results Data saturation was achieved after 18 interviews. All participants reported having access to the Internet, but only a few described using the Internet to obtain general information or to conduct online purchases. Most participants described barriers to Internet use which included: a lack of interest, knowledge and confidence, a fear of technology and no trust in social media sites. Facilitators of Internet use included family encouragement and attending community groups which taught computer use. Female participants reported valuing the social contact provided by attending such groups. The Internet was seen as a source of health information once a GP had diagnosed a physical problem, but was not considered a source of information about distress or mood problems. Participants did not use the Internet to access social support and described a preference for face-to-face communication. Conclusions GPs need to understand how an individual patient utilises the Internet. GPs should explore the self-management strategies already employed by older adults experiencing distress and understand that directing these older people to online support might not be acceptable. Encouraging distressed older adults to attend computer group classes might be useful as this permits face-to-face social contact, and may help to facilitate Internet use in the future.